On Definition of a Formal Model for IEC 61499 Function Blocks. (11th November 2007) - Dubinin, Victor; Vyatkin, Valeriy
Abstract : Formal model of IEC 61499 syntax and its unambiguous execution semantics are important for adoption of this international standard in industry. This paper proposes some elements of such a model. Elements of IEC 61499 architecture are defined in a formal way following set theory notation. Based on this description, formal semantics of IEC 61499 can be defined. An example is shown in this paper for execution of basic function blocks. The paper also provides a solution for flattening hierarchical function block networks.